Experimental Study of Rotor-Stator Contact Cycles. (23rd June 2021) - Chipato, Elijah T; Shaw, Alexander D; Friswell, Michael I; Sánchez Crespo, Rafael
Abstract: A rotor can contact a stator thereby inducing some very strong non-linearities that can result in a plethora of vibration phenomena. Synchronous motions, chaotic motion, backward whirl, forward whirl are some of the reported phenomena in the literature. This article presents an experimental approach based on a very flexible rotor rig designed with drill string dynamics in mind for rotordynamic experiments. A non-contact technique was used for data acquisition using a consumer-grade Go-Pro Hero 6 Black camera which captures a series of images(video) which are then post-processed using MATLAB's image processing toolbox to understand the nature of dynamics involved. A mathematical model of the experimental rig was used for comparison with the actual experiment to assess the effectiveness of the data acquisition procedure used and validity of the model. The model is able to a good extent to reproduce the behaviour of the test rig. The fundamental phenomena exhibited by the system is analysed and discussed based on bifurcation plots, spectral intensity plots and orbit plots visualised in both rotating and stationary frame.